Effects of Metolachlor, Oxyfluorfen and Picloram on Cellulose Decomposition in a Peat Soil under Laboratory Conditions - Sahid, Ismail; A., Ramli; Z., Razali (Universiti Putra Malaysia Press, 1995)
The effects of the three herbicides, metolachlor, picloram and oxyfluorfen on cellulose decomposition were studied in a peat soil in laboratory experiments. The herbicides were either sprayed on to cellulose substrate before burial or incorporated directly into the soil. The herbicides applied directly to the substrates before burial reduced the decomposition of the substrate more than those applied to the soil. Pre-incubation of the treated soil for 4 weeks before burial slightly increased the decomposition rate after 6 or 12 weeks of incubation.